Factors Affecting Domestic Violence against Rural Educated and Uneducated Women in Bangladesh: A Sociological Analysis (American Journal of Youth and Women Empowerment, 2024)
All societal and economic strata are negatively impacted by the problem of domestic violence. Although the government of Bangladesh is making efforts to address the problem of domestic violence, the nation is ranked fourth worldwide for violence against women. Thus, the purpose of this study is to explore the pattern and causes of domestic violence against rural educated and uneducated women in Bagerhat district of Bangladesh. In this study, district and upazila were selected purposively whereas union, village and respondents were selected using simple random sampling technique. Using random sample procedures, a total of 100 rural women were chosen. The data was analyzed using tabular, graphical, and descriptive statistics. It is found from the socioeconomic analysis of the study that the mean age of the rural women in the study area is 29.05 years. In terms of educational status, it is seen that 13% respondents had primary education while 19% had secondary education with the average years of schooling of women is 6.23 years. It is observed that 35% women were housewife, 15% were NGO worker and10% health worker. Findings of the study reveal that husband was the main culprit for committing domestic violence against women in 64% cases while sister-in-law are responsible for committing violence in 16% cases. Findings of the study indicate that 28% educated women experienced physical violence whereas 78% uneducated women experienced physical violence in their life. In case of women affected by psychological violence, it is seen that 58% educated women affected by psychological violence while 64% uneducated women affected by physical torture violence. In terms of women affected by economic violence, it is seen that uneducated women (86%) are more affected than educated women (42%). Result of the study shows that 38% educated women and 56% uneducated women believe that poverty is responsible for committing domestic violence against women. Considering media violence as a cause of domestic violence, it is observed that 56% educated women and 55% uneducated women believe media violence is responsible for domestic violence against women. In addition, 57% educated women and 59% uneducated women believe that marital conflict is a main factor which are contributing domestic violence against women.